Enhancing the efficiency of coagulation method for sewage treatment by adding sludge - Peng Zhao; Lin Li; Xilei Song; Miaokui Wang; Zhengan Zhang; Yuying Li; Yu Zhao; B. Larry Li (PLoS ONE, 2025)
The high performance sedimentation tank (HPST) is an efficient water treatment technology, which accelerates the settling rate of flocculates by adding sludge, so as to increase the water treatment load of coagulation sedimentation tank. Its sewage treatment effect is affected by many factors such as sludge dosage, wastewater pH, flocculant dosage, stirring time, settling time, etc. This paper was to study the optimal conditions of HPST, first, some single-factor tests were conducted to preliminarily explore the optimal range of influencing factors, and then response surface methodology (RSM) tests were performed to accurately determine the optimums of significant factors.The results showed that adding sludge can not improve the water quality of coagulation treatment, but it can significantly accelerate the coagulation settlement process, the sludge dosage, the coagulant dosage and sewage pH all impacted significantly on its coagulation effect, and existed inflection points. A model that could guide HPST was obtained by RSM tests. The model optimization and experimental validation showed that the optimal HPST conditions for treating domestic sewage were as follows: the dosage of polyaluminum chloride (PAC) was 1.70 g/L, cationic polyacrylamide (CPAM) dosage was 2.35 mg/L, sewage pH was maintained at 8.0, sludge dosage was 10 mL/L, stirring time lasted for 5 minutes, and settling time lasted for 30 minutes. As a result of these optimized conditions, the turbidity of treated sewage decreased to 1.19 NTU.